Leading Causes of Death for Older Asian Americans - Huo, MD, PhD, Dezheng; Lauderdale, PhD, Diane S. (North American Journal of Medicine and Science, 2009)
Asian Americans are the fastest growing population in US, but data describing their disease burden are limited. For most US health statistics, Asian Americans are grouped into a single race category. We use a unique data file to identify causes of death for persons aged 65 or older in six Asian American ethnic subgroups (Chinese, Indians, Japanese, Koreans, Filipinos, and Vietnamese). Causes of death classified by the International Classification of Diseases, Tenth Revision (ICD–10) are ranked according to the number of deaths assigned to each cause. There are a total of 76,866 death records included in this study. The 10 leading causes of death account for 85% of all deaths for Asian Americans and the top 3 causes (heart disease, cancer, and stroke) account for 68%. The rankings and relative cause-specific mortalities varied significantly across the six Asian ethnic groups. Indians had the highest relative burden of heart disease (41.6% of all deaths), followed by Filipinos (35.6%), then the other four Asian ethnic groups ( 30%). Cancer, the second leading cause of death, accounted for about 26% of all deaths for Chinese, Japanese, Koreans and Vietnamese, 21% for Filipinos and 18% for Indians. Influenza and pneumonia, chronic lower respiratory disease, diabetes, accidents (unintentional injuries), and kidney disease also ranked among the top 10 causes, but the specific ranks vary across ethnic populations. Differences in the ranking are also evident by age and sex. Because of significant heterogeneity among Asian American ethnic groups, it is more informative to calculate ethnicity-specific rankings of causes of death.